Trials of passion : crimes committed in the name of love and madness - Appignanesi, Lisa (Pegasus Crime, 2015)
"A journey into the heart of dark passions and the crimes they impel, and their trial by daylight and doctors. When passion is in the picture, what is criminal, what is sane, what is mad or simply bad? Through court and asylum records, letters and newspaper accounts, this book brings to life some sensational trials between 1870 and 1914, a period when the psychiatric professions were consolidating their hold on our understanding of what is human. Outside fiction, individual emotions and the inner life had rarely been publicly discussed: now, in an increasingly popular press and its courtroom reports, people avidly consumed accounts of transgressive sexuality, savage jealousy and forbidden desires. These stood revealed as aspects not only of those labelled mad, but potentially, of everyone. With great storytelling flair and a wealth of historical detail, Lisa Appignanesi teases out the vagaries of passion and the clashes between the law and the clinic as they stumble towards a (sometimes reviled) collaboration. Sexual etiquette and class roles, attitudes to love, madness and gender, notions of respectability and honor, insanity and lunacy, all are at play in that vital forum in which public opinion is shaped--the theater of the courtroom" --